1998
DOI: 10.1007/s004120050316
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the wheat Ph1 locus on chromatin organisation and meiotic chromosome pairing analysed by genome painting

Abstract: The Ph1 locus in wheat influences homo(eo)logous chromosome pairing. We have analysed its effect on the behaviour and morphology of two 5RL rye telosomes in a wheat background, by genomic in situ hybridisation (GISH), using rye genomic DNA as a probe. Our main objective was to study the effect of different alleles of the Ph1 locus on the morphology and behaviour of the rye telosomes in interphase nuclei of tapetal cells and in pollen mother cells at early stages of meiosis. The telosomes, easily detectable at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 46 publications
3
47
3
Order By: Relevance
“…The level of associations in pairs increased in the course of prophase I but the frequencies observed in zygotene and pachytene were lower than the corresponding frequencies in the wild type. We interpret this as being in agreement with a delay in the initiation and development of synapsis in the absence of a functional Ph1 allele, known to exist in wheat (Mikhailova et al 1998;Maestra et al 2002). Homologous centromeres in the 2Brc-2R pair were separated in 97 and 100% of Ph11 and Ph1À cells at leptotene, respectively, and their association level did not increase in the course of prophase I.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The level of associations in pairs increased in the course of prophase I but the frequencies observed in zygotene and pachytene were lower than the corresponding frequencies in the wild type. We interpret this as being in agreement with a delay in the initiation and development of synapsis in the absence of a functional Ph1 allele, known to exist in wheat (Mikhailova et al 1998;Maestra et al 2002). Homologous centromeres in the 2Brc-2R pair were separated in 97 and 100% of Ph11 and Ph1À cells at leptotene, respectively, and their association level did not increase in the course of prophase I.…”
Section: Resultssupporting
confidence: 86%
“…In leptotene, telomeres migrate to form a tight cluster and centromeres appear as compact structures. Chromatin undergoes a conformational change that results in chromosome elongation (Mikhailova et al 1998;Maestra et al 2002), which is apparent in centromere signals at the leptotene-zygotene transition. As synapsis progresses in midzygotene, the telomere bouquet disintegrates (Holm 1986).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main regulator, Ph1, was discovered 50 years ago (Riley and Chapman, 1958;Sears and Okamoto, 1958) and only recently characterized at the molecular level (Griffiths et al, 2006;Al-Kaff et al, 2007). However, the very peculiar nature of the Ph1 locus, which consists of a cluster of cyclin-dependant kinases (cdk-like genes) and a segment of subtelomeric heterochromatin, does not readily explain the multiple cytological effects attributed to Ph1 (Feldman, 1993;Mikhailova et al, 1998;Martinez-Perez et al, 2003;Prieto et al, 2005;Corredor et al, 2007). On the other hand, Ph2, another suppressor of homoeologous associations (Upadhya and Swaminathan, 1967;MelloSampayo, 1971), was shown to affect synaptic progression (Martinez et al, 2001) but the genes responsible for the phenotype are still to be identified (Sutton et al, 2003).…”
Section: Introductionmentioning
confidence: 99%